Carla Bley - Beal, Amy C. (American composers., 2011)
This is the first comprehensive treatment of the remarkable music and influence of Carla Bley, a highly innovative American jazz composer, pianist, organist, band leader, and activist. With fastidious attention to Bley's diverse compositions over the last fifty years spanning critical moments in jazz and experimental music history, Amy C. Beal tenders a long-overdue representation of a major figure in American music._x000B__x000B_Bley is best known for her jazz opera "Escalator over the Hill," her role in the Free Jazz movement of the 1960s, and her collaborations with artists such as Jack Bruce, Don Cherry, Robert Wyatt, and Pink Floyd drummer Nick Mason. She has successfully maneuvered the field of jazz creating works that range from the highly accessible and tradition-based to commercially unviable and avant-garde. Beal details the staggering variety in Bley's work as well as her use of parody, quotations, and contradictions, examining the vocabulary Bley has developed throughout her career and highlighting the compositional and cultural significance of her experimentalism._x000B__x000B_Beal also points to Bley's professional and managerial work as a pioneer in the development of artist-owned record labels, the cofounder and manager of WATT Records, and the cofounder of New Music Distribution Service. Showing her to be not just an artist but an activist who has maintained musical independence and professional control amid the profit-driven, corporation-dominated world of commercial jazz, Beal's straightforward discussion of Bley's life and career will stimulate deeper examinations of her work.